Intra-operative anaesthetic management of older patients undergoing liver surgery. (March 2021) - Wallace, Hilary; Miller, Thomas; Angus, William; Stott, Matthew
Abstract: Older patients represent a growing proportion of the general surgical caseload. This includes those undergoing liver resection, with figures rising faster than the rate of population ageing. The physiology of ageing leads to changes in all body systems which may render the provision of safe anaesthesia more challenging than in younger patients. Anaesthesia for liver surgery has specific principles, largely aimed at reducing venous bleeding from the liver, and those related to complex major surgery. This review explores the principles of anaesthesia for liver resection and describes how they may require modification in the older patient. The traditional approach of low central venous pressure anaesthesia in order to reduce bleeding may need to be altered in the presence of a cardiovascular system less able to tolerate hypotension and hypoperfusion. These changes in physiology should also lower the threshold for invasive monitoring. The provision of effective analgesia perioperatively should be tailored to minimise the surgical stress response and opiate use. Careful consideration of general principles of intra-operative care for older patients, such as positioning, drug dosing, avoidance of excessively deep anaesthesia, and maintenance of normothermia are also important given the prolonged, complex nature of liver surgery. This individualised approach, with careful attention to changes in physiology allows liver resections to be undertaken in older patients without increases in mortality.